Measurement of Monosaccharides and Conversion of Glucose to Acetate in Anoxic Rice Field Soil - Chidthaisong, Amnat (American Society for Microbiology, 1999)
Degradation of glucose has been implicated in acetate production in rice field soil, but the abundance of glucose, the temporal change of glucose turnover, and the relationship between glucose and acetate catabolism are not well understood. We therefore measured the pool sizes of glucose and acetate in rice field soil and investigated the turnover of [U-(14)C]glucose and [2-(14)C]acetate. Acetate accumulated up to about 2 mM during days 5 to 10 after flooding of the soil. Subsequently, methanogenesis started and the acetate concentration decreased to about 100 to 200 μM. Glucose always made up >50% of the total monosaccharides detected. Glucose concentrations decreased during the first 10 days from 90 μM initially to about 3 μM after 40 days of incubation. With the exception at day 0 when glucose consumption was slow, the glucose turnover time was in the range of minutes, while the acetate turnover time was in the range of hours. Anaerobic degradation of [U-(14)C]glucose released [(14)C]acetate and (14)CO(2) as the main products, with [(14)C]acetate being released faster than (14)CO(2). The products of [2-(14)C]acetate metabolism, on the other hand, were (14)CO(2) during the reduction phase of soil incubation (days 0 to 15) and (14)CH(4) during the methanogenic phase (after day 15). Except during the accumulation period of acetate (days 5 to 10), approximately 50 to 80% of the acetate consumed was produced from glucose catabolism. However, during the accumulation period of acetate, the rate of acetate production from glucose greatly exceeded that of acetate consumption. Under steady-state conditions, up to 67% of the CH(4) was produced from acetate, of which up to 56% was produced from glucose degradation.